Analisis Keputusan Konsumen Terhadap Pembelian Ayam Goreng (Studi Kasus Perusahan X di Kabupaten Jember) - Hariadi Subagja; Estin Roso Pristiwaningsih; Joko Irsan Sanyoto; Agus Hadi Prayitno (Politeknik Negeri Jember, 2018)
This research aimed to know consider of consumer to decide of buying fried chicken and to know the dominan factor what it influence of buying decision in x company. The research was conducted at the two outlets, they were Gajah Mada street Number 74 dan Roxy Square Hayam wuruk street, Jember. The research method used was survey wtih 75 respondents that took by purposive sampling. The data result were analyzed using multiple linear regression analysis, F-test, and t-test. The result of analysis showed Y= 3,040 - 0,103X1 + 0,473X2 + 0,060X3 + 0,133X4 + 1,170X5. That equation means every level of consumer buying decision by X1 (price) equal to -0,103, X2 (taste) equal to 0,473, X3 (promotion) equal to 0,060, X4 (life style) equal to 0,133, and X5 (desain interior) equal to 1,170. The result of F-test showed that all of variabels has significant.Â